Inhibitory Effect of 1,8-Cineol on β-Catenin Regulation, WNT11 Expression, and Cellular Progression in HNSCC - Roettger, Anna; Bruchhage, Karl-Ludwig; Drenckhan, Maren; Ploetze-Martin, Kirsten; Pries, Ralph; Wollenberg, Barbara (Frontiers in Oncology, 2017)
Objectives Head and neck squamous cell carcinoma (HNSCC) is one of the most common tumors worldwide. The high mortality rates have not changed during the last three decades, and thus there is an enormous need for innovative therapy approaches. Several recent studies suggest an important role of the Wnt/β-catenin signaling pathway in the tumorigenesis of HNSCC. We analyzed the effect of the monoterpene oxide 1,8-cineol on the regulation of the Wnt/β-catenin signaling pathway and the cellular progression of different HNSCC cell lines. Methods Permanent HNSCC cell lines were exposed to varying concentrations and times of 1,8-cineol. Regulation and activity profiles of the Wnt/β-catenin signaling cascade were analyzed using Western hybridization experiments, MTT assays, real-time PCR-based epithelial to mesenchymal transition array, and immunohistochemistry. Results Exposure of different cell lines to 1,8-cineol treatment resulted in a dose-dependent inhibition of proliferation and a decreased activity of the WNT/β-catenin pathway. We can show the inhibition of glycogen synthase kinase 3 (GSK-3)α/β (Ser-9/21) as well as a corresponding decreased endolysosomal localization, leading to a decreased β-catenin activity. Furthermore, we can show that exposure to cineol functionally results in a reduced expression of WNT11. Conclusion In this work, we demonstrate for the first time that 1,8-cineol acts as an inhibitor of the Wnt/β-catenin activity in HNSCC via a decreased inhibition of GSK-3, which lead to reduced levels of WNT11 and a dose-dependent decrease of the cellular progression. Our data represent a new mechanism of 1,8-cineol activity, which may lead to novel molecular targets and treatment approaches of this natural drug.